Development of E-Modules on Puberty Materials to Train Digital Literacy of Madrasah Ibtidaiyah Learners : Pengembangan E-modul Pubertas Untuk Melatihkan Literasi Digital Peserta Didik Madrasah Ibtidaiyah - Astuti, Yanti; Suyidno, Suyidno; Suryajaya, Suryajaya; Jamilah, Nor (Universitas Muhammadiyah Sidoarjo, 2024)
Digital literacy development is needed to live, learn and work in the era of digital technology. However, this literacy is lacking in schools. Therefore, this research aims to produce a puberty e-module using project-based learning that is feasible to improve students' digital literacy. The research design was adapted from Tessmer's formative evaluation model, which is limited to self-evaluation, expert review and one-to-one evaluation. Data collection techniques used e-module validation instruments by 3 experts and 2 practitioners and content readability assessments by students. The results showed the validation results in the aspects of design, format, material, language, presentation, and innovation were 94, 97, 94, 98, 94, and 98 with very valid criteria. In addition, the readability of the e-module content with very practical criteria. Thus, the puberty e-module using project-based learning developed is feasible to use to improve students' digital literacy. Pengembangan literasi digital dibutuhkan untuk hidup, belajar, dan bekerja di era teknologi digital. Namun, literasi tersebut kurang dilatihkan di sekolah. Oleh karena itu, tujuan penelitian ini adalah menghasilkan e-modul pubertas menggunakan project-based learning yang layak digunakan untuk meningkatkan literasi digital peserta didik. Desain penelitian ini diadaptasi dari evaluasi formatif model Tessmer, yang dibatasi pada self evaluation, expert review dan one to one evaluation. Teknik pengumpulan data menggunakan instrumen validasi e-modul oleh 3 pakar dan 2 praktisi, serta penilaian keterbacaan isi oleh peserta didik. Hasil penelitian menunjukkan hasil validasi pada aspek desain, format, materi, kebahasaan, penyajian, dan inovasi berturu-turut sebesar 94, 97, 94, 98, 94, dan 98 dengan kriteria sangat valid. Selain itu, keterbacaan isi e-modul dengan kriteria sangat praktis. Dengan demikian, e-modul pubertas menggunakan project-based learning yang dikembangkan adalah layak digunakan untuk meningkatkan literasi digital peserta didik